Revealing Food Fulfillment Threads and Innovative Technology for Enhancing Rice Productivity and Ensuring the Food Security in Indonesia - Hibatullah, Fairus Hisanah; Raidasari, Fatharani; Triana, Aurelia Puspa; Siagian, Verita Kristi Lydia; Simarmata, Tualar (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Ensuring food security by Indonesia's Golden Year in 2045 presents a formidable challenge, with advancements in agricultural technology anticipated to play a crucial role in attaining this goal. Rice is the major food crop in Indonesia, and its consumption is still considerably high, indicating that daily nutrient uptake relies on its grain. However, the current population of Indonesia demanding rice is 31.2 million tons and this number of populations will grow at the rate of 0.41 percent. The rice consumption of the Indonesian people is quite high, namely 114.6 kg per person per year. The rice harvest area in 2023 decreased by 2.45%, from 10.45 million hectares to 10.20 million hectares, resulting in rice production which also decreased from 31.54 million tons to 30.90 million tons. The average conversion of paddy fields to non-harvest areas in Indonesia reached 100,000 hectares per year. Meanwhile, the average ability to print rice fields is only 60,000 hectares a year. This means that there is a difference in the conversion of paddy fields of around 40,000 hectares per year. Therefore, the purpose of this study is to elucidate how agricultural technology can enhance rice production across different land types in Indonesia, thus supporting food security efforts. To achieve the objectives of this research, a systematic literature review method was used. The result of this study shows that the amalgamation of diverse technological advancements and innovative practices in rice cultivation holds immense promise in bolstering productivity, bolstering sustainability, and tackling nutritional deficiencies. Prospectively, the use of cutting-edge technology offers some insights that can be input for policy formulation, technological innovation, and community engagement strategies aimed at creating a safer, fairer, and more sustainable food future for Indonesia to achieve food security by 2045.